2012
DOI: 10.1002/ajim.22137
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure and mortality among workers at three titanium dioxide plants

Abstract: There was no indication of a positive association between occupational exposure and death from all causes, all cancers, lung cancers, non-malignant respiratory disease, or all heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…Of the seven studies, two reported that lung cancer risk was significantly elevated among the workers (Boffetta et al, 2004;Ellis et al, 2013). When these positive findings were further investigated, it was apparent that exposure-response relationships were not observed for the exposure metrics evaluated (e.g., duration of employment, cumulative exposure).…”
Section: Human Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Of the seven studies, two reported that lung cancer risk was significantly elevated among the workers (Boffetta et al, 2004;Ellis et al, 2013). When these positive findings were further investigated, it was apparent that exposure-response relationships were not observed for the exposure metrics evaluated (e.g., duration of employment, cumulative exposure).…”
Section: Human Datamentioning
confidence: 99%
“…1). Upon further evaluation, seven studies were determined to fulfill the inclusion criteria and quantitatively characterized carcinogenic endpoints in humans (Boffetta et al, 2001(Boffetta et al, , 2004Chen and Fayerweather, 1988;Ellis et al, 2010Ellis et al, , 2013Fryzek et al, 2003;Ramanakumar et al, 2008). These studies were all epidemiologic assessments of workers in TiO 2 production facilities in Europe and in the United States.…”
Section: Human Datamentioning
confidence: 99%
See 3 more Smart Citations